Inoculação de bactérias diazotróficas em genótipos de sorgo sacarino - Skolaude, Alex Caitan (2014)
The sweet sorghum (Sorghum bicolor) presents high potential to be utilized as a raw material for the generation of ethanol. Recent studies indicated that sorghum can be colonized by diazotrophic bacteria that may provide part of the necessary crop N through biological N fixation (BNF). Therefore, the present study was aimed to evaluate the efficiency of inoculation with diazotrophic bacteria in sweet sorghum genotypes for growth, biomass production, stalk yield and N accumulation. Two studies were conducted. The first study was conducted in a greenhouse where fifteen sorghum genotypes were grown under four N sources i.e, control (without any N source), Herbaspirillumrubrisubalbicans, Azospirillum brasilense and 60 kg N ha-1. The second study was conducted in the field for two consecutive years with four sorghum genotypes under five sources of N: control (without any N source); A. brasilense;40 kg N ha-1 (40 N) + A. brasilense; 40 kg N ha-1 and 80 kg N ha-1 (80 N). In both studies, biometric variables of growth, dry matter, biomass and total N accumulation were evaluated besides sugarcane stalk and grain head yield in the field study. In both studies there was no interaction between genotypes and N sources.In the first study, the best results were obtained with the inoculation of Azospirillum brasilense which promoted an increase in dry matter (MSR), plant height, stalk diameter and N accumulation of 30%, 9 %, 10% and 8%, respectively, compared to control. In the second study, the genotype BRS 511 had high stalk production and grain head and low plant height and higher average stalk diameter which minimized the risk of lodging , Inoculation of plants did not increase the variables analyzed, except the production of grain head. The isolated use of inoculant resulted in production of similar grain head that was obtained with 40N treatment. Combined use of inoculant with N (40N) resulted in an increase of 6% in grain head production compared to treatment 40N and reached to 93% obtained with 80N treatment. The results of this study indicated a positive effect of inoculation with Azospirillumbrasilense on the production of grain head in sweet sorghum.